Glocal-Case Study to Improve Critical Thinking Skills: Komodo National Park Case Study - Lala, Sofia Godeliva Un; Widodo, Wahono; Subrata, Heru; Mariana, Neni (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
The need for an initial understanding of critical thinking skills in students is very important. However, research has shown that most students still lack this ability, which highlights the importance of effective teaching methods to improve critical thinking skills in students. Therefore, this study aims to determine the ability of Case Study in the Glocal context to improve students' critical thinking skills. A quasi-experimental methodology was used, involving 34 female students and 14 male students in the fifth semester as participants. This study administered the Critical Thinking Skill Test (CTS) treatment to students, followed by paired and unpaired t-tests to examine the impact of the Glocal-Case Study model on their critical thinking skills. The results showed that Glocal-Case Study significantly improved students' critical thinking skills more than traditional instruction. The experimental group outperformed the control group in the post-test, indicating the effectiveness of Glocal-Case Study . Therefore, this study recommends the implementation of the Glocal-Case Study model by lecturers in global perspective courses to improve students' understanding of glocal problem solving.